L. pseudomesenteroides and L. johnsonii isolated from yaks in Tibet modulate gut microbiota in mice to ameliorate enteroinvasive Escherichia coli-induced diarrhea. (July 2019) - Wang, Yaping; Li, Aoyun; Liu, Juanjuan; Mehmood, Khalid; Wangdui, Basang; Shi, Hongmei; Luo, Xiaolin; Zhang, Hui; Li, Jiakui
Abstract: Enteroinvasive Escherichia coli (EIEC) are well-known food-borne pathogens that cause animal intestinal diseases. Lactobacillus is believed to inhibit intestinal pathogens and maintain a healthy gut microbiota. This study aimed to investigate the effects of pre-supplementation of Lactobacillus from yaks (4500m) to prevent the clinical symptoms and the improvement of the disordered flora caused by E. coli infection. Forty healthy mice were randomized to four study groups (n = 10); Leuconostoc pseudomesenteroides (LP1), Lactobacillus johnsonii (LJ1), blank control, and control groups. Mice in the LP1, LJ1, and control groups were intraperitoneally challenged with EIEC O124 (1 × 10 9 CFU) on day 23. After two days, the mice in control group were recorded for high mortality. The diarrhea in LP1 and LJ1 groups was much lower than that in the control group, and no death was recorded. In histopathology, pre-supplementation of LJ1 and LP1 relieved the damage to the liver, spleen and duodenum caused by E. coli . In addition, the normal intestinal microecology was also affected by infection of EIEC, including an increase in relative abundance of Proteobacteria . At the same time, the beneficial bacteria were increased and harmful bacteria were decreased in different intestinal segments of the LJ1 and LP1 groups compared to the control group. In conclusion, pre-supplementation of LP1 and LJ1 can mitigate EIEC-induced intestinal flora dysbiosis and can also reduce EIEC-associated diarrhea. Highlights: Lactobacillus strains with good probiotic potential were isolated from Tibetan yaks. Pre-supplementation of L. johnsonii & L. pseudomesenteroides could effectively alleviate diarrhea & clinical symptoms caused by E. coli. LJ1 and LP1 promoted a healthy microbiome in diarrheic mice.